Feasibility and Successful Enrollment in a Proof-of-Concept HIV Prevention Trial of VRC01, a Broadly Neutralizing HIV-1 Monoclonal Antibody. (1st May 2021) - Edupuganti, Srilatha; Mgodi, Nyaradzo; Karuna, Shelly T.; Andrew, Philip; Rudnicki, Erika; Kochar, Nidhi; deCamp, Allan; De La Grecca, Robert; Anderson, Maija; Karg, Carissa; Tindale, India; Greene, Elizabeth; et al.
Abstract : Background: The Antibody-Mediated Prevention trials (HVTN 704/HPTN 085 and HVTN 703/HPTN 081) are the first efficacy trials to evaluate whether VRC01, a broadly neutralizing monoclonal antibody targeting the CD4-binding site of the HIV envelope protein, prevents sexual transmission of HIV-1. HVTN 704/HPTN 085 enrolled 2701 cisgender men and transgender (TG) individuals who have sex with men at 26 sites in Brazil, Peru, Switzerland, and the United States. Methods: Participants were recruited and retained through early, extensive community engagement. Eligible participants were randomized 1:1:1 to 10 mg/kg or 30 mg/kg of VRC01 or saline placebo. Visits occurred monthly, with intravenous (IV) infusions every 8 weeks over 2 years, for a total of 10 infusions. Participants were followed for 104 weeks after first infusion. Results: The median HVTN 704/HPTN 085 participant age was 28 years; 99% were assigned male sex; 90% identified as cisgender men, 5% as TG women and the remaining as other genders. Thirty-two percent were White, 15% Black, and 57% Hispanic/Latinx. Twenty-eight percent had a sexually transmitted infection at enrollment. More than 23, 000 infusions were administered with no serious IV administration complications. Overall, retention and adherence to the study schedule exceeded 90%, and the dropout rate was below 10% annually (7.3 per 100 person-years) through week 80, the last visit for the primary end point. Conclusions: HVTN 704/HPTN 085 exceeded accrual and retention expectations. With exceptional safety of IV administration and operational feasibility, it paves the way for future large-scale monoclonal antibody trials for HIV prevention and/or treatment.